The Unity of Life and Art in Classical Daoism - Poškaitė, Loreta (Acta Orientalia Vilnensia, 2000)
The aim of this paper is to reveal the unity of art and life in classical Daoism as the characteristic feature of Chinese aesthetic being. Chinese concept of art and creativity, the process of art creativity and its psychological methods as well as the realisation in the art of painting for the purpose will be discussed. The most particular ontological feature of Dao is the inter–relatedness of being and non–being which manifests itself in aesthetic way of “non–connective life”. This unity has become the main ideal in the art of painting which constitutes its sacredness as well as connection with secular life. Such connection is revealed through the concept of joy (le) and sense of humour which is important feature of aesthetic being in Daoism as the most optimistic affirmation of life.